Prevalence of subclinical mastitis and associated risk factors at cow and herd level in dairy farms in North-West Ethiopia - Mekonnen, S A; Koop, G; Melkie, S T; Getahun, C D; Hogeveen, H; Lam, T J G M (Elsevier BV, 2017)
Knowledge of mastitis pathogens and their predominance as well as understanding of risk factors are prerequisites to improve udder health in a herd, region or country. In Ethiopia, such information is scarce, despite the fact that mastitis is an important cattle disease in the country. A cross-sectional study that describes prevalence and causative agents of subclinical mastitis (SCM) as well as risk factors at cow and herd level was conducted on 167 dairy farms in North-West Ethiopia. On average, 33% of the quarters and 62% of the cows were California Mastitis Test (CMT) positive, but the within herd quarter level prevalence ranged between 0 and 100%. A total of 1543 milk samples, being 27 quarters that showed signs of CM, 606 CMT positive quarters and 910 CMT negative quarters were cultured, respectively 40%, 67% and 47% was positive on bacteriological culture. Coagulase negative staphylococci (CNS) (31%) followed by Staphylococcus aureus (9%) were the pathogens most frequently isolated. Based on face-to-face questionnaire data, 35 herd level and 13 cow level factors were evaluated for their association with SCM (based on CMT) and with a positive culture for any bacteria, CNS or S. aureus. Cows with a history of CM, of higher parity, >150days in milk (DIM) and herds with owners that have >10th grade level of education had higher odds of SCM. The odds of being culture positive for any bacteria was higher in cows with ≥25% Holstein Friesian blood level (HBL), >150 DIM, housed on cemented floors, and milked by squeezing rather than stripping. Similarly, the odds of culturing CNS was higher in cows with 25-50% HBL, >150 DIM, and milked by squeezing. Staphylococcus aureus was more often found in cows with a history of CM and in larger herds. Checking the udder for mastitis, feeding cows according to their requirements and allowing calves to suckle the cows were negatively associated with SCM, with culturing any bacteria and with culturing CNS, respectively. Higher odds of SCM and of culturing CNS were found in herds owned by members of a dairy cooperative. In summary, we identified a high prevalence of SCM and intramammary infections with substantial variation between farms, and we found a number of risk factors explaining this variation. The risk factors for mastitis that were identified in this study can form the basis of an udder health control program specific for the dairy industry in North-West Ethiopia.
Keywords: Intramammary infection; Dairy; Ethiopia; Risk factor; Mastitis; Taverne